Bone marrow morphology: a critical diagnostic tool in secondary hemophagocytic lymphohistiocytosis - Abdul Halim, Sarah; A.Talib, Norlelawati; Ibrahim, Ismail; Adzahar, Sumaiyah (2025)
Introduction: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory syndrome characterised by excessive immune activation and systemic inflammation. Timely diagnosis remains challenging due to nonspecific clinical presentations and overlapping laboratory abnormalities, particularly in secondary HLH where underlying triggers such as infections obscure the clinical picture. Bone marrow morphology can offer essential diagnostic evidence in such cases. Case Report: A 77-yearold man with squamous cell carcinoma of the lung and recent COVID-19 infection presented with pancytopenia and progressive clinical deterioration. Initial investigations were inconclusive and bone marrow examination was performed as part of pancytopenia workup. The bone marrow aspirate and trephine biopsy revealed prominent hemophagocytic activity. The calculated H-Score was 171, supporting a diagnosis of HLH. Immunohistochemistry showed strong CD68 and CD163 expression, with Glycophorin A confirming erythrophagocytosis. Despite initiation of corticosteroid therapy, the patient developed multiorgan failure and died. Discussion: This case highlights the diagnostic value of bone marrow morphology in identifying HLH, particularly when clinical features are ambiguous or overlapping with other conditions. The morphological evidence of haemophagocytosis, supported by immunohistochemical markers, was critical in establishing the diagnosis. In resource-limited settings or cases with diagnostic uncertainty, timely bone marrow assessment can expedite recognition and initiation of treatment. While haemophagocytosis alone is not pathognomonic, its presence within the appropriate clinical context strongly supports the diagnosis and may improve clinical decision-making. This approach is particularly valuable in secondary HLH cases where underlying conditions may complicate the clinical picture and delay recognition of this rapidly progressive, potentially fatal syndrome.